PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS DAN RISIKO SISTEMATIS TERHADAP NILAI PERUSAHAAN - Verado, Sandy; Kurniawati (Indonesian Journal of Accounting and Governance, 2021)
The main purpose of this study is to analyze firm value from non financial, financial and economic macro perspective which proxied by corporate social responsibility, profitability, and systematic risk. The research data came from the final sample of 10 Indonesia companies, 7 Malaysian companies and 11 Singapore companies listed in Global Reporting Initiative (GRI) database and stock exchange in each country during 2015-2017. Results of this study indicate that only profitability shows the positive impact on firm value, while corporate social responsibility and systematic risk have no effect. In addition, the Kruskal – Wallis test results show that there are no significant differences in corporate social responsibility, profitability and systematic risk in Indonesia, Malaysia and Singapore.